(untitled) (Heritage, 2022)
The CSTO operation in Kazakhstan during 2022 hadn`t only a charachet of building peace mission, but also has the purpose to prevent violent political coup in the form of color revolution in this, for russian interest strategic important post-Soviet republic. Beside that, this CSTO operation had essential and crucial importance for the preservation of Kazakhstan constitutional order, and also prevented the constitution of a new geopolitical framework and order in the extremely challenging region of Central Asia. Through the research work on the analysis of this operation, interesting data on the refractions of various factors of the foreign policies of Russia, China, the United States and Turkey through Kazakhstan were obtained. Also, article reveals the cause and effect relationship between the complex political and security events in Kazakhstan, primarly through the prism of radical Islamist factor which played an active role in kazakstanian scenario, particularly if we have in mind withdrawal of the American contigent from Afghanistan. American focus since than has been placed in Eurasian circle, bearing in mind strengthening project of created by Russia, known as Eurasian security and economic integrations.